معالم العرفان فی دروس القرآن میں صوفی عبدالحمید سواتی کے اسلوب اور خصوصیات کا جائزہ: An Analysis of the Style and Distinctive Features of Sufi Abdul Hamid Swati in Ma‘alim ul-Irfan fi Duroos ul-Qur’an DOI: https://doi.org/10.5281/zenodo.17694289 (Khairulummah, 2024)
This study critically examines the stylistic features and methodological approach of Sufi Abdul Hamid Swati in his Quranic commentary Ma‘alim al-Irfan fi Duroos al-Qur’an. The research highlights his distinctive expository style, marked by clarity, simplicity, and coherence, and his methodological framework that integrates classical Tafsir principles with insights from Hadith and the sayings of the Sahaba. It also explores how Swati contextualizes Quranic teachings within spiritual, ethical, and social dimensions, reflecting his Sufi orientation and addressing contemporary moral and social issues. The analysis shows that his approach maintains textual fidelity while promoting spiritual reflection, offering valuable guidance for scholars and students of Islamic studies. Overall, the study provides an insightful perspective on his contribution to Quranic exegesis within a Sufi and analytical paradigm.
Keywords: Tafsir Methodology, Sufi Exegesis, Ma‘alim al-Irfan, Stylistic Analysis, Quranic Interpretation, Analytical Study